2016
DOI: 10.3847/0004-637x/828/2/105
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Spectral and Optical Properties of a Ulx in NGC 4258 (M106)

Abstract: We study the X-ray and optical properties of the ultraluminous X-ray source (ULX) X-6 in the nearby galaxy NGC 4258 (M106) based on the archival XMM-Newton, Chandra, Swift, and Hubble Space Telescope (HST) observations. The source has a peak luminosity of L X ∼ 2 × 10 39 erg sin the XMM-Newton observation of 2004 June. Consideration of the hardness ratios and spectral model parameters shows that the source seems to exhibit possible spectral variations throughout the X-ray observations. In the images from the H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…The F 𝑥 / F 𝑜 𝑝𝑡 ratio was calculated in the range of 1.96 − 2.30 for three optical candidates of X7. These rates quite similar to other ULX's optical candidates (Feng & Kaaret 2008;Tao et al 2011;Yang et al 2011;Avdan et al 2016;Aksaker et al 2019).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The F 𝑥 / F 𝑜 𝑝𝑡 ratio was calculated in the range of 1.96 − 2.30 for three optical candidates of X7. These rates quite similar to other ULX's optical candidates (Feng & Kaaret 2008;Tao et al 2011;Yang et al 2011;Avdan et al 2016;Aksaker et al 2019).…”
Section: Resultssupporting
confidence: 78%
“…The studies in the optical band showed that majority of the ULXs are found to be associated with star forming regions or star clusters (Patruno & Zampieri 2010;Grisé et al 2011;Poutanen et al 2013;Avdan et al 2016Avdan et al , 2019Egorov et al 2017;Urquhart et al 2018). These associations were supported by the counterparts of ULXs as early type OB stars due to their observed blue color (Liu et al 2004;Grisé et al 2005;Soria et al 2005;Roberts et al 2008;Poutanen et al 2013).…”
Section: Introductionmentioning
confidence: 93%
“…By making use of large and up to-date ground based and Hubble Space Telescope (HST), optical counterparts of about 20 ULXs have been identified (e.g. Grisé et al 2008;Yang et al 2011;Gladstone et al 2013;Motch et al 2014;Avdan et al 2016b;Urquhart & Soria 2016;Vinokurov et al 2018). Such studies give important hints to estimate the origin of optical emission, which has strong contribution from the accretion disk as well as donor star.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have studied the environments around these five ULXs in the NGC4490/4485 galaxies. The correlation between ULX source positions and stellar clusters has been already noticed in the literature (see Kaaret et al 2004;Abolmasov et al 2007a;Grise et al 2012;Avdan et al 2016a). Several authors have suggested that some ULXs might have their clusters already dispersed due to their ages (Liu et al 2007;Poutanen et al 2013).…”
Section: Discussionmentioning
confidence: 59%